CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, LEVERAGE DAN REAL ERNINGS MANAGEMENT - Adi, Yohana Epifani Kartika; Kusumaningtyas, Metta (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2020)
Investors always use various information to get maximum profit in investing activities. This study aims to examine the effect of corporate governance, firm size and leverage on real earnings management. Corporate governance is proxied by institutional ownership, the proportion of the independent board of commissioners, and the number of audit committee meetings. The sample of this research is 90 consumer goods industry companies listed on the Indonesia Stock Exchange, which were selected using a purposive sampling method during the 2014-2018 research period. The analysis technique used is multiple linear regression. The results of the study conclude that institutional ownership, the proportion of the independent board of commissioners and the number of audit committee meetings have no effect on real earnings management. However, firm size and leverage have a positive effect on real earnings management.